Development of nanofiltration flat sheet membrane for biorefinery application - Boon Huey, Teow (2015)
In recent years, biorefining and bioenergy production have received considerable attention as an alternative way to renewable bioresources to produce similar energy and chemicals derived from fossil energy sources which represents a more sustainable path in the bioeconomy. Biomass residues available from forest, crops and agricultural processing are the main source for the production value added chemicals such as xylitol, ethanol, furfural and various sugars by acid-catalyzed hydrolysis. Hydrolyzed product normally contains mixture of sugar that needs to separate depending on the final target product. Several separation techniques can be used to separate the sugar component such as membrane based separation, chromatographic and molecular imprinting polymer. In the current study, nanofiltration (NF) flat sheet membranes were developed based on the different compositions of PES/NMP/PVP which are from 23 to 30 wt% PES. The membrane was tested for the separation of glucose, xylose and acetic acid. From the result obtained, acetic acid and glucose retentions were up to 90% while xylose retention up to 80%. Meanwhile, the separation factor of xylose to glucose was more than 1 for 28 wt% PES whiles the separation factor of acetic acid to xylose and glucose were less than 1 for 30 wt% PES.